The efficiency levels of the nurse managers in communication - (:unkn) unknown (SCIENCEPARK SCI, ORGANIZATION & COUNSELING LTD, 2018)
Aim is to predicate efficiency levels of the nurse managers in communication. The sample constituted 108 nurses. The socio-demographical characteristics of the nurses and the nurse managers were inquired. The efficiency levels of the nurse managers in communication were evaluated with the 'Communication Efficiency Scale'. SPSS for Windows 12.0 Program was used in the data evaluation. When the demographical characteristics of nurse managers have been compared with communication level, there was not found a statistically significant correlation (p > 0.05). But the nurse managers who are over 40 ages, license grad and had a long time professional experience were found conspicuous because of their high communication scores. As a result, it was determined that the 'Communication Efficiency Scale' is reliable and valid and can be used in these studies and the efficiency levels of the nurse managers who work in a Training and Research Hospital in Istanbul are enough.
Keywords: Nurse; manager; communication; scale